At Korg Berlin: Office Objects - Takahashi, Tatsuya; Glup, Verena; Melnyk, Samantha (Berlin Korg, 2024)
"Curious about what we get up to when we aren’t making instruments? This book is all about celebrating the joy of making things. Inside its contents are 21 office objects found in the KORG Berlin space, ranging in scale from coat hooks to speakers to storage units. These designs are made open-source with dimensioned drawings and a list of materials with their associated cost. Our book is meant to inspire those who wish to build, instead of buy, the objects you surround yourself with." -https://korg.berlin/products/bookofdesigns
Keywords: Technology; Acoustics; Interior design; Catalog